Education Relying on "the General Plan of Educational System for Surveying Religious Training in the First Two Decades of Islamic Revolution: Based on Islamic Republic of Iran" - Hojatollah Abasi (پژوهش در آموزش معارف و تربیت اسلامی)
The present study has been conducted with the purpose of surveying foundations, purposes, and principles, of religious training, in the first two decades of Islamic revolution revolving around "the general plan of education system in Islamic Republic of Iran" using qualitative content analysis. Exploring upstream documents with the purpose of recognizing the root of defects in the past as well as likely defects in future in terms of religious training are among the most important necessities for conducting this research. After Islamic revolution, along with the change of philosophy dominant in the education system in Iran, families left the issues of their children's training to the only formal and public educational institute in the country. It is while the reports indicate weakness in religious training to students at different levels. The results of this research show that religious training is derived from Islamic instructions in two fields of beliefs and religion, while the document under study regards religious training equal to Islamic training which is an inexpert outlook on this subject. Although some basics, principles, and objectives have generally and vaguely been raised in this regard, not enough attention has been paid to the field of religious training. The analysis and conclusion of the results show that the approach of religious education in the above document is not integrative that is per se one of the most fundamental causes for weakness in the religious training of students.